Enzymatically cross-linked skim milk powder: Enhanced rheological and functional properties. (February 2021) - Romeih, Ehab; Albadarin, Ahmad B.; Olaleye, Akeem; Walker, Gavin
Abstract: Enzymatically cross-linking milk proteins by microbial transglutaminase (MTGase) is a promising strategy in developing and promoting desired multi-functional properties of dairy foods. This study evaluated the effect of MTGase treatments (0.5, 1, 2 and 4 U g −1 milk protein) of skim milk at two different incubation conditions (20 min at 38 °C, 12 h at 4 °C) on rheological and structural characteristics of spray dried skim milk powders (SMP). SMP samples treated with MTGase showed significantly increased particle size. Cross-linking milk proteins by MTGase revealed significant improvements in powder flowability characteristics by means of lower aeration and basic flow energies, and higher bulk density and compressibility properties compared with the control SMP. Overall, cross-linked SMP offers a promising option as a multi-functional ingredient for the dairy and/or composite food producers, and appearing to be an efficient option in improving powder rheological properties for dairy powder manufacturers.